Pengaruh Likuiditas, Risiko Kredit Dan Pemulihan Ekonomi Nasional Dimasa Pandemi Covid-19 Terhadap Profitabilitas Bank Perkreditan Rakyat (BPR) Se BAKORWIL 1 Periode 2020-2021 - Indrian Supheni; Hermiliani Olpah; Rohmatul Khusnan; Budiono Budiono (Edumedia Solution, 2022)
Rural Banks (BPR) are banks whose role is to collect and distribute funds to the public. The main objective of BPR is to gain profitability. The researcher aims to determine the effect of liquidity (LDR), credit risk (NPL), the recovery of the National Economy during the Covid 19 pandemic on profitability (ROA) at BPRs throughout the East Java Regional Coordinating Board during the 2020-2021 period. The research method uses a descriptive quantitative approach. A population of 53 BPRs registered with the OJK are located in Bakorwil I East Java. The sampling technique using purposive sampling obtained 34 companies that meet the criteria. The data used by the researcher is secondary data for the quarterly financial statements for the 2020-2021 period. The data analysis technique used the normal distribution test as the main prerequisite and the multiple linear regression analysis test. Based on statistical evidence, the researcher concludes that the liquidity variable (LDR) and national economic recovery during the Covid 19 pandemic have a significant effect on profitability (ROA) at BPRs throughout the East Java Regional Coordination Board for the period 2020-2021. Meanwhile, credit risk (NPL) cannot have a significant effect on profitability (ROA) at BPRs throughout the East Java Regional Coordination Board for the period 2020-2021.